No easy way out [videorecording] (Cleveland, Ohio American Portrait Films, 1994)
A combination of a drama of the anguish of a young girl as she travels the road of pregnancy and abortion, and interviews with teens, parents, doctors, and others about abortion.
Keywords: Pregnancy; Abortion